Building New Spaces - Gemma Ventura; Agnès Garcia‑Ventura (Arabian Humanities)
In this paper we concentrate mainly on the sociocultural configuration in Rajā’ al‑Ṣāni‘’s Banāt al‑Riyāḍ through the analysis of language and gender. Combining these two approaches we propose that al‑Ṣāni‘’s novel is an example of subversion in different ways: in the novel itself, through its use of languages, through gender subversion, and through the invasion of physical and symbolic arenas. On the one hand, we focus on the use of languages and the combination of different registers and formats used in the text. On the other hand, we deal with the construction of characters, focusing on their gender roles and how these are at the same time accepted and contested.